Evolusi dan strategi public relations dalam membangun reputasi organisasi di era modern - Asqolani, Ahmad Maulana Kholil Muhajir Madani (Maliki Interdisciplinary Journal, 2025)
This study examines the evolution and strategies of Public Relations (PR) in building organizational reputation in the modern era. Digital transformation has transformed the role of PR from merely conveying information to managing strategic communications focused on reputation. This study utilizes a literature review method, referencing six relevant journals, covering the role of PR in the digital era, SWOT analysis, crisis management, media relations, corporate social responsibility (CSR), and the balance between technical and managerial roles. The results indicate that PR plays a crucial role in maintaining a positive organizational image through effective communication, utilizing digital technology, and strengthening relationships with the media and the public. However, challenges such as reputation crises, the spread of negative information, and the dominance of technical roles remain major obstacles. Therefore, PR needs to strengthen its managerial capacity, digital literacy, and strategic analysis skills to serve as a key advisor in organizational decision-making. Thus, PR plays a role not only as a communications implementer but also as a key driver in building public trust and a sustainable reputation in the global era.